Flexicurity: a strategy for sustainable socio-economic recovery - Pasnicu Daniela (European Regional Science Association (ERSA), 2010)
Social partners have different visions about flexicurity both conceptual point of view and of some the eventual mechanisms of implementing this concept. They have in mind the implementation of flexicurity only in their interest area, some of them are emphasasing flexibility while other social security, so there isn't a global agreement. A sound balance between flexibility and security is an indispensable means of improving competitiveness while maintaining the European social model. The combination of flexibility and security is unique to each country and in the context of the present crises calls for a strengthening security for workers. The present paper adds some new elements to the existing research on flexicurity by exploring the relevance and adaptability of this strategy to the Romanian labor market. The present paper also emphasizes that social dialogue is a key component for elaborate a Romanian flexicurity model, adaptable to the labor market dynamics, non-birocratic, that can generate new and better work places and open the way to a sustainable straightening. As a result the paper includes conceptual clarifications regarding flexicurity, an analysis of the Romanian labor market flexicurity, the role of the flexicurity in reducing the effects of the economic crisis and the principal conclusions from the social partners' point of views which were presented in the public audition organized on this topic.
Keywords: 330